„LauRa - In der Lehramtsausbildung Reflexionskompetenz analysieren“ : Untersuchungen zum Verhältnis von Theorie, Praxis und Reflexion im Rahmen der Professionalisierung angehender Lehrpersonen - Meier, Jana

Die Kraft der Bilder. Funktionen neuer Illustrationen bei Übersetzungen. Kathleen Vereecken – Alles komt goed, altijd (2018) | Alles wird gut, immer (2021) - Lammer, Christina
Keywords: Kathleen Vereecken; Kinder- und Jugendliteratur; Krieg; Belgien

Dequantizing the Quantum Singular Value Transformation: Hardness and Applications to Quantum Chemistry and the Quantum PCP Conjecture - Gharibian, Sevag; Gall, François Le (Proceedings of the 54th ACM Symposium on Theory of Computing (STOC))
The Quantum Singular Value Transformation (QSVT) is a recent technique that gives a unified framework to describe most quantum algorithms discovered so far, and may lead to the development of novel quantum algorithms. In this paper we investigate the hardness of classically simulating the QSVT. A recent result by Chia, Gily\'en, Li, Lin, Tang and Wang (STOC 2020) showed that the QSVT can be efficiently "dequantized" for low-rank matrices, and discussed its implication to quantum machine learning. In this work, motivated by establishing the superiority of quantum algorithms for quantum chemistry and making progress on the quantum PCP conjecture, we focus on the other main class of matrices considered in applications of the QSVT, sparse matrices. We first show how to efficiently "dequantize", with arbitrarily small constant precision, the QSVT associated with a low-degree polynomial. We apply this technique to design classical algorithms that estimate, with constant precision, the singular values of a sparse matrix. We show in particular that a central computational problem considered by quantum algorithms for quantum chemistry (estimating the ground state energy of a local Hamiltonian when given, as an additional input, a state sufficiently close to the ground state) can be solved efficiently with constant precision on a classical computer. As a complementary result, we prove that with inverse-polynomial precision, the same problem becomes BQP-complete. This gives theoretical evidence for the superiority of quantum algorithms for chemistry, and strongly suggests that said superiority stems from the improved precision achievable in the quantum setting. We also discuss how this dequantization technique may help make progress on the central quantum PCP conjecture.

Turn all the lights off: Bright- and dark-field second-harmonic microscopy to select contrast mechanisms for ferroelectric domain walls - Hegarty, Peter A.; Beccard, Henrik; Eng, Lukas M.; Rüsing, Michael (Journal of Applied Physics)
Recent analyses by polarization resolved second-harmonic (SH) microscopy have demonstrated that ferroelectric (FE) domain walls (DWs) can possess non-Ising wall characteristics and topological nature. These analyses rely on locally analyzing the properties, directionality, and magnitude of the second-order nonlinear tensor. However, when inspecting FE DWs with SH microscopy, a manifold of different effects may contribute to the observed signal difference between domains and DWs, i.e., far-field interference, Čerenkov-type phase-matching (CSHG), and changes in the aforementioned local nonlinear optical properties. They all might be present at the same time and, therefore, require careful interpretation and separation. In this work, we demonstrate how the particularly strong Čerenkov-type contrast can selectively be blocked using dark- and bright-field SH microscopy. Based on this approach, we show that other contrast mechanisms emerge that were previously overlayed by CSHG but can now be readily selected through the appropriate experimental geometry. Using the methods presented, we show that the strength of the CSHG contrast compared to the other mechanisms is approximately 22 times higher. This work lays the foundation for the in-depth analysis of FE DW topologies by SH microscopy.
Keywords: General Physics and Astronomy

Nonlinear optical interactions in focused beams and nanosized structures - Amber, Zeeshan H.; Spychala, Kai J.; Eng, Lukas M.; Rüsing, Michael (Journal of Applied Physics)
Thin-film materials from μm thickness down to single-atomic-layered 2D materials play a central role in many novel electronic and optical applications. Coherent, nonlinear optical (NLO) μ-spectroscopy offers insight into the local thickness, stacking order, symmetry, or electronic and vibrational properties. Thin films and 2D materials are usually supported on multi-layered substrates leading to (multi-)reflections, interference, or phase jumps at interfaces during μ-spectroscopy, which all can make the interpretation of experiments particularly challenging. The disentanglement of the influence parameters can be achieved via rigorous theoretical analysis. In this work, we compare two self-developed modeling approaches, a semi-analytical and a fully vectorial model, to experiments carried out in thin-film geometry for two archetypal NLO processes, second-harmonic and third-harmonic generation. In particular, we demonstrate that thin-film interference and phase matching do heavily influence the signal strength. Furthermore, we work out key differences between three and four photon processes, such as the role of the Gouy-phase shift and the focal position. Last, we can show that a relatively simple semi-analytical model, despite its limitations, is able to accurately describe experiments at a significantly lower computational cost as compared to a full vectorial modeling. This study lays the groundwork for performing quantitative NLO μ-spectroscopy on thin films and 2D materials, as it identifies and quantifies the impact of the corresponding sample and setup parameters on the NLO signal, in order to distinguish them from genuine material properties.<
Keywords: General Physics and Astronomy

Ba(BO2OH) – A Monoprotonated Monoborate from Hydroflux Showing Intense Second Harmonic Generation - Li, Yuxi; Hegarty, Peter A.; Rüsing, Michael; Eng, Lukas M.; Ruck, Michael (Zeitschrift für anorganische und allgemeine Chemie)
Abstract Pure samples of colorless, air‐stable Ba(BO 2 OH) crystals were obtained from Ba(NO 3 ) 2 and H 3 BO 3 under the ultra‐alkaline conditions of a KOH hydroflux at about 250 °C. The product formation depends on the water‐base molar ratio and the molar ratio of the starting materials. B(OH) 3 acts as a proton donor (Brønsted acid) rather than a hydroxide acceptor (Lewis acid). Ba(BO 2 OH) crystallizes in the non‐centrosymmetric orthorhombic space group P 2 1 2 1 2 1 . Hydrogen bonds connect the almost planar (BO 2 OH) 2− anions, which are isostructural to HCO 3 − , into a syndiotactic chain. IR and Raman spectroscopy confirm the presence of hydroxide groups, which are involved in weak hydrogen bonds. Upon heating in air to about 450 °C, Ba(BO 2 OH) dehydrates to Ba 2 B 2 O 5 . Moreover, the non‐centrosymmetric structure of Ba(BO 2 OH) crystals was verified with power‐dependent confocal Second Harmonic Generation (SHG) microscopy indicating large conversion efficiencies in ambient atmosphere.
Keywords: Inorganic Chemistry

Tuning the Čerenkov second harmonic contrast from ferroelectric domain walls via anomalous dispersion - Hegarty, Peter A.; Eng, Lukas M.; Rüsing, Michael (Journal of Applied Physics)
Second harmonic (SH) microscopy represents a powerful tool for the investigation of crystalline systems, such as ferroelectrics and their domain walls (DWs). Under the condition of normal dispersion, i.e., the refractive index at the SH wavelength is larger as compared to the refractive index at the fundamental wavelength, n(2ω)>n(ω), bulk crystals will generate no SH signal. Should the bulk, however, contain DWs, an appreciable SH signal will still be detectable at the location of DWs stemming from the Čerenkov mechanism. In this work, we demonstrate both how SH signals are generated in bulk media and how the Čerenkov mechanism can be inhibited by using anomalous dispersion, i.e., n(ω)<n(2ω). This allows us to quantitatively estimate the relative strength of the Čerenkov compared to other SH contrast mechanisms in DWs, such as the interference contrast. The results are in agreement with previous experiments based on the geometric separation of the signals. Due to the observed, strong Čerenkov contrast, such signal contributions may not be neglected in polarimetry studies of ferroelectric DWs in the future.
Keywords: General Physics and Astronomy

Ein Blick auf: Verstetigung und Transfer im Bundesprogramm „Kita-Einstieg: Brücken bauen in frühe Bildung“ - Albers, Timm; Hoeft, Maike; Abendroth, Sonja; Meusel, Sarah

Erkenntnisse zu Verstetigung und Transfer im Bundesprogramm "Kita-Einstieg: Brücken bauen in frühe Bildung" - Abendroth, Sonja; Hoeft, Maike; Meusel, Sarah

SA-SDR: A Novel Loss Function for Separation of Meeting Style Data - von Neumann, Thilo; Kinoshita, Keisuke; Boeddeker, Christoph; Delcroix, Marc; Haeb-Umbach, Reinhold (ICASSP 2022 - 2022 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP))

MMS-MSG: A Multi-purpose Multi-Speaker Mixture Signal Generator - Cord-Landwehr, Tobias; von Neumann, Thilo; Boeddeker, Christoph; Haeb-Umbach, Reinhold (2022 International Workshop on Acoustic Signal Enhancement (IWAENC))
The scope of speech enhancement has changed from a monolithic view of single, independent tasks, to a joint processing of complex conversational speech recordings. Training and evaluation of these single tasks requires synthetic data with access to intermediate signals that is as close as possible to the evaluation scenario. As such data often is not available, many works instead use specialized databases for the training of each system component, e.g WSJ0-mix for source separation. We present a Multi-purpose Multi-Speaker Mixture Signal Generator (MMS-MSG) for generating a variety of speech mixture signals based on any speech corpus, ranging from classical anechoic mixtures (e.g., WSJ0-mix) over reverberant mixtures (e.g., SMS-WSJ) to meeting-style data. Its highly modular and flexible structure allows for the simulation of diverse environments and dynamic mixing, while simultaneously enabling an easy extension and modification to generate new scenarios and mixture types. These meetings can be used for prototyping, evaluation, or training purposes. We provide example evaluation data and baseline results for meetings based on the WSJ corpus. Further, we demonstrate the usefulness for realistic scenarios by using MMS-MSG to provide training data for the LibriCSS database.

Monaural source separation: From anechoic to reverberant environments - Cord-Landwehr, Tobias; Boeddeker, Christoph; von Neumann, Thilo; Zorila, Catalin; Doddipatla, Rama; Haeb-Umbach, Reinhold (2022 International Workshop on Acoustic Signal Enhancement (IWAENC))
Impressive progress in neural network-based single-channel speech source separation has been made in recent years. But those improvements have been mostly reported on anechoic data, a situation that is hardly met in practice. Taking the SepFormer as a starting point, which achieves state-of-the-art performance on anechoic mixtures, we gradually modify it to optimize its performance on reverberant mixtures. Although this leads to a word error rate improvement by 7 percentage points compared to the standard SepFormer implementation, the system ends up with only marginally better performance than a PIT-BLSTM separation system, that is optimized with rather straightforward means. This is surprising and at the same time sobering, challenging the practical usefulness of many improvements reported in recent years for monaural source separation on nonreverberant data.

Rezension von: Viola Schrader: Historisches Denken und sprachliches Handeln. Eine qualitativ-empirische Untersuchung von Schülertexten. Münster et al.: LIT 2021 - Hartung, Olaf (sehepunkte)

On Synchronization of Wireless Acoustic Sensor Networks in the Presence of Time-Varying Sampling Rate Offsets and Speaker Changes - Gburrek, Tobias; Schmalenstroeer, Joerg; Haeb-Umbach, Reinhold (ICASSP 2022 - 2022 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP))

Warping of Radar Data Into Camera Image for Cross-Modal Supervision in Automotive Applications - Grimm, Christopher; Fei, Tai; Warsitz, Ernst; Farhoud, Ridha; Breddermann, Tobias; Haeb-Umbach, Reinhold (IEEE Transactions on Vehicular Technology)
We present an approach to automatically generate semantic labels for real recordings of automotive range-Doppler (RD) radar spectra. Such labels are required when training a neural network for object recognition from radar data. The automatic labeling approach rests on the simultaneous recording of camera and lidar data in addition to the radar spectrum. By warping radar spectra into the camera image, state-of-the-art object recognition algorithms can be applied to label relevant objects, such as cars, in the camera image. The warping operation is designed to be fully differentiable, which allows backpropagating the gradient computed on the camera image through the warping operation to the neural network operating on the radar data. As the warping operation relies on accurate scene flow estimation, we further propose a novel scene flow estimation algorithm which exploits information from camera, lidar and radar sensors. The proposed scene flow estimation approach is compared against a state-of-the-art scene flow algorithm, and it outperforms it by approximately 30% w.r.t. mean average error. The feasibility of the overall framework for automatic label generation for RD spectra is verified by evaluating the performance of neural networks trained with the proposed framework for Direction-of-Arrival estimation.

Technically enabled explaining of voice characteristics - Wiechmann, Jana; Glarner, Thomas; Rautenberg, Frederik; Wagner, Petra; Haeb-Umbach, Reinhold (18. Phonetik und Phonologie im deutschsprachigen Raum (P&P))

Long‐term effects of institutional conditions on perceived corruption – A study on organizational imprinting in post‐communist countries - Auer, Thorsten Fabian; Knorr, Karin; Thommes, Kirsten (Business Ethics, the Environment & Responsibility)
In this paper, we apply imprinting theory to examine how institutional transformation substantially influences perceptions of corruption that we argue to be incorporated to a varying extent in organizations founded in that period. For this purpose, we compare the effect of a sudden shock (dissolution of the Soviet Union) on the managers' present perceptions to that of a steady transition (EU accession). We consult the 5th round of the Business Environment and Enterprise Performance Survey from 2012 to 2014 analyzing 4715 interviews with managers of organizations from twelve Central and Eastern European countries. Our results reveal striking differences in the present perception of corruption for organizations founded immediately before and immediately after these institutional transitions. The study's results contribute to the research on imprinting theory regarding the relationship between organizations and institutional conditions that constitutes a lasting effect on organizational structures. Thus, applying an institutional perspective that considers less stable periods for organizations yields a promising avenue in research on organizational behavior.
Keywords: Central and Eastern Europe; corruption; imprinting theory; institutional transformation; shock-imprinting

Die Wirksamkeit von Lernzielen für Studienleistungen – eine experimentelle Studie - Auer, Thorsten Fabian (die hochschullehre)
According to the German Rectors’ Conference (HRK), German higher education teaching fails to meet the demand to integrate competence-oriented learning objectives. Despite a wide-ranging debate on the use of learning objectives, empirical research on their effectiveness is scarce. The present study uses the features of digital teaching platforms to investigate the perception and effectiveness of learning objectives applying a randomised controlled experiment followed by a survey in a course for undergraduate economics students (N = 30). Controlling group preconditions and the treatment effect allows to draw conclusions about the different learning outcomes of the student groups. The specification of behaviour-oriented learning objectives in the online course system leads to significantly better performance in the treatment group. A stronger perception of the learning objectives in the treatment group supports this effect that remains significant in a regression analysis. Thus, the study provides an empirical justification to integrate learning objectives in university teaching.
Keywords: learning objectives; academic performance; perception; teaching methods; experiment

An approach to teaching data science in middle school - Podworny, Susanne; Fleischer, Yannik (Proceedings of the 15th international conference on technology in mathematics teaching (ICTMT 15))

Teaching machine learning with decision trees in middle school using CODAP - Fleischer, Yannik; Podworny, Susanne (Proceedings of the 15th international conference on technology in mathematics teaching (ICTMT 15))

An example of rich, real and multivariate survey data for use in school - Podworny, Susanne; Fleischer, Yannik; Stroop, Dietlinde; Biehler, Rolf

Lydia Böttger (Universität Paderborn) rezensiert: Michalak, Magdalena; Döll, Marion (Hrsg.) (2021): Lehrwerke und Lehrmaterialien im Kontext des Deutschen als Zweitsprache und der sprachlichen Bildung. [Deutsch als Zweitsprache Positionen, Perspektiven, Potenziale, Bd. 2]. Münster, New York: Waxmann, 164 Seiten. ISBN 978-3-8309-4105-7. - Böttger, Lydia (www.daz-portal.de)

Investigation into Target Speaking Rate Adaptation for Voice Conversion - Kuhlmann, Michael; Seebauer, Fritz; Ebbers, Janek; Wagner, Petra; Haeb-Umbach, Reinhold (Interspeech 2022)

Schorsch Kamerun: „Extra Vages machen wir aus tiefer Überzeugung“. - Jacke, Christoph (Kaput. Magazin für Insolvenz & Pop.)

Effective vocabulary learning apps: what should they look like? An evaluation with a particular view to German language acquisition - Lentfort, Theresa; Künzl-Snodgrass, Annemarie; de Vincent-Humphreys, Maren (Ab Initio Language Teaching in British Higher Education. The Case of German)

Informed vs. Blind Beamforming in Ad-Hoc Acoustic Sensor Networks for Meeting Transcription - Gburrek, Tobias; Schmalenstroeer, Joerg; Heitkaemper, Jens; Haeb-Umbach, Reinhold (2022 International Workshop on Acoustic Signal Enhancement (IWAENC))

A Meeting Transcription System for an Ad-Hoc Acoustic Sensor Network - Gburrek, Tobias; Boeddeker, Christoph; von Neumann, Thilo; Cord-Landwehr, Tobias; Schmalenstroeer, Joerg; Haeb-Umbach, Reinhold

Threshold Independent Evaluation of Sound Event Detection Scores - Ebbers, Janek; Haeb-Umbach, Reinhold; Serizel, Romain (Proceedings of the IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP))
Performing an adequate evaluation of sound event detection (SED) systems is far from trivial and is still subject to ongoing research. The recently proposed polyphonic sound detection (PSD)-receiver operating characteristic (ROC) and PSD score (PSDS) make an important step into the direction of an evaluation of SED systems which is independent from a certain decision threshold. This allows to obtain a more complete picture of the overall system behavior which is less biased by threshold tuning. Yet, the PSD-ROC is currently only approximated using a finite set of thresholds. The choice of the thresholds used in approximation, however, can have a severe impact on the resulting PSDS. In this paper we propose a method which allows for computing system performance on an evaluation set for all possible thresholds jointly, enabling accurate computation not only of the PSD-ROC and PSDS but also of other collar-based and intersection-based performance curves. It further allows to select the threshold which best fulfills the requirements of a given application. Source code is publicly available in our SED evaluation package sed_scores_eval.

KI im Einsatz. Interdisziplinäre Herausforderungen im Projekt UAV-Rescue - Philippi, Martina; Heusinger-Heß, Victoria; Ari, Meral; Krüger, Emily (Mensch und Computer 2022 - Workshopband)
Im Projekt „UAV-Rescue: UAV-getragene Sensorik zur KI-basierten Unterstützung von Rettungsmissionen“ wird an einem unbemannt fliegenden System geforscht, das in schwer zugänglichen Räumen bei der Rettungspriorisierung hilft, indem es den Einsatzkräften eine Visualisierung des Raumes mit darin lokalisierten Lebenszeichen zur Verfügung stellt. Diese neue Technologie wirft verschiedene ethische Fragestellungen auf, die unter anderem die Nutzung von Künstlicher Intelligenz zur Lebenszeichendetektion und die Einbettung der neuen Technologie in die Einsatzpraxis betreffen. Die ethische Begleitforschung des Projekts adressiert diese Fragestellungen in einem interdisziplinären und iterativen Diskurs mit Technikpartnern und Endanwendern. Einige dieser Fragestellungen werden hier vor dem Hintergrund der eingesetzten KI-Methoden und der bestehenden Einsatzpraxis beim THW vorgestellt.
Keywords: rescue robotics; interdisciplinarity; artifical intelligence; ethics

Same Different but not Same Same: Ethnic Discrimination in Application Procedures in the German Public Sector - Auer, Thorsten Fabian; Ekemen, Helin; Hagedorn, Carolin; Heise, Chantal; Rese, Christine (Empirical Economics Letters)
Regulations to prevent ethnic discrimination in accessing the labor market are implemented most thoroughly in the public sector. However, it remains to be assessed if these regulations are internalized. We conducted a field experiment to examine ethnic discrimination when applying for internships in German municipalities by unsolicited inquiries. We compared responses in German cities to Turkish, Italian, and German applicants in two periods, and find consistent disadvantages for the Turkish and Italian applicants as well as differences related to gender. Thus, the likelihood for ethnic discrimination rises when applying for positions in public institutions that are not subject to regulations.
Keywords: Ethnic Discrimination; Public Sector; Field Experiment; Application Procedure

Auswirkung der Theologie auf das rechtsphilosophische Denken der Muʿtazila: Lektüre bei al-Qāḍī ʿAbd al-Ǧabbār - Abdelrahem, Mohammed (Zeitschrift für Recht und Islam / Journal of Law & Islam)
Im Wesentlichen wird im Beitrag die Frage beantwortet, inwieweit die muʿtazilitisch-rationale Theologie die Rechtsphilosophie ʿAbd al-Ǧabbārs beeinflusst. Vor allem werden als Beispiele die Auseinandersetzung ʿAbd al-Ǧabbārs mit den verschiedenen Rechtsquellen und deren Aspekte systematisch-rechtlich dargestellt und die Frage nach der Zentralität des Menschen, dessen Vernunft und Wohl fokussiert. Dafür bedient sich der Beitrag der uṣūlitischen Werke und Beiträge ʿAbd al-Ǧabbārs, in denen dieser eine besondere, von seinem kalām-Ansatz stark geprägte Methodologie verfolgt. Mit seinen uṣūl-Werken konstruierte der šāfiʿitische Muʿtazilit ʿAbd al-Ǧabbār, Systematiker der muʿtazilitischen Dogmenlehre, eine rechtsphilosophische, rational geprägte Theorie und gilt damit als eine der bedeutendsten ›Stationen‹ auf dem Weg der Methodologie der Theolog:innen sowie des Verhältnisses zwischen der kalām-Lehre und den uṣūl al-fiqh. Bei seiner Beschäftigung mit den verschiedenen Rechtsquellen des islamischen Rechts führt er drei Voraussetzungen für ihre gesetzgebende Funktion an. Dabei handelt es sich um Aspekte, die die Rechtsbelege zu berücksichtigen haben und somit eine Art ethische Perspektive bilden: den Menschen als Empfänger des normativen Texts, die Vernunft als Instrument der Rechtswahrnehmung und das Wohl der Menschen als Ziel der Rechtsbelege.

Smart cities and smart governance models for future cities - Nastjuk, I.; Trang, S.; Papageorgiou, E. (Electronic Markets)

Konzeptpapier zur Konferenz "Geschichte im digitalen Wandel? Geschichtskultur – Erinnerungspraktiken – Historisches Lernen"

Produktkennzeichnung durch lokal definierte Einstellung von ferromagnetischen Eigenschaften beim Drückwalzen von metastabilen Stahlwerkstoffen - Arian, Bahman; Homberg, Werner; Kersting, Lukas; Trächtler, Ansgar; Rozo Vasquez, Julian (36. Aachener Stahlkolloquium – Umformtechnik “Ideen Form geben“)

A flow forming process model to predict workpiece properties in AISI 304L - Arian, Bahman; Oesterwinter, Annika; Homberg, Werner; Rozo Vasquez, Julian; Walther, Frank; Kersting, Lukas; Trächtler, Ansgar (19th Int. Conference on Metal Forming 2022)

"Die Bombardierung von Brüssel - teil 2" (Podcast) - Huybrechts, Yves

"Das Museum der BSD in Soest. Ein Interview mit Burkhard Schnettler" - Huybrechts, Yves

Autonomes Putten mittels datengetriebener und physikbasierter Methoden - Junker, Annika; Fittkau, Niklas; Timmermann, Julia; Trächtler, Ansgar (Proceedings - 32. Workshop Computational Intelligence: Berlin, 1. - 2. Dezember 2022)

Zum Potential von Lernmaterial für den Einsatz im konfessionell-kooperativen Religionsunterricht: eine qualitative Inhaltsanalyse von Unterrichtsentwürfen zum Thema Märtyrerinnen und Märtyrer - Hüster, Jonas Maximilian

Kooperation von Elternhaus und Schule zum Thema "digitale Medien". Unterschiede zwischen Elternhäusern und Zusammenhänge mit elterlichen Fähigkeiten zur Nutzung und Gestaltung des Internets sowie Medienerziehung - Bonanati, Sabrina; Kurock, Ricarda; Gruchel, Nicole; Buhl, Heike M. (MedienPädagogik)
Die Kooperation zwischen Elternhaus und Schule kann Eltern in ihren Fähigkeiten zur Internetnutzung und -gestaltung sowie in der Wahl passender Medienerziehungsstrategien ihrer Kinder unterstützen. Voraussetzung dafür ist Wissen darüber, welche Kooperationsangebote Eltern von Schulen zum Thema digitale Medien erhalten. Die vorliegende Studie untersuchte anhand einer Befragung von N = 736 Schülerinnen und Schülern der fünften Klassenstufe und N = 426 ihrer Eltern, welche Informations- und Teilhabeangebote letztere erhielten und wie diese Angebote mit elterlichen Fähigkeiten zur Nutzung und Gestaltung des Internets sowie Medienerziehung zusammenhängen. Eltern erhielten nur zum Teil Informations- und Teilhabeangebote zum Thema ‹digitale Medien›. Eltern mit Migrationshintergrund und Eltern mit niedrigeren bis mittleren Bildungsabschlüssen berichteten aber, häufiger Angebote zu erhalten. Je häufiger Eltern Angebote erhielten, bei denen sie digitale Medien mit ihren Kindern zusammen ausprobieren und erproben konnten, umso geringer waren Fähigkeiten zur Internetnutzung. Dies kann mit der Passung der Angebote von Schulen zu den Bedürfnissen von Eltern zusammenhängen, aber auch ein Anzeichen dafür sein, dass gerade Eltern mit geringeren Fähigkeiten auf Kooperationsangebote von Schulen eingehen. Es wurden keine signifikanten Zusammenhänge zwischen Kooperationsangeboten und Medienerziehung gefunden. Ergebnisse können helfen, vermehrte Angebote für Eltern zu schaffen sowie adressatengerecht zu gestalten.

Family Climate and Social Adaptation of Adolescents in Community Samples: A Systematic Review - Kurock, Ricarda; Gruchel, Nicole; Bonanati, Sabrina; Buhl, Heike M. (Adolescent Research Review)
The family plays an important role in adolescents’ social development. Yet there is little information about the impact of family climate on adolescents’ social adaptation, and the term “family climate” is seldom clearly defined and is usually related to other concepts, such as family systems or family environments. To understand the core of family climate, this study conducted a systematic review to analyze research about family climate associated with adolescents’ social adaptation in community samples. A search of empirical research published over the last 20 years identified 12 relevant studies. The studies revealed that family climate can mainly be described in terms of cohesion, conflict, organization, adaptability, and expressiveness. Family climate was shown to be a good predictor of both problem-solving skills and violence in relationships and exhibited further associations with other aspects of social adaptation. This review revealed a need for more systematic and longitudinal research on family climate in community samples.
Keywords: Family environment; Family system; Adolescents; Social adaptation; Systematic review

Einleitung - Haacke-Werron, Stefanie; Karsten, Andrea; Scharlau, Ingrid (Reflexive Schreibwissenschaft. Disziplinäre und praktische Perspektiven)

Sprechen, Schreiben, Denken - Karsten, Andrea (Reflexive Schreibwissenschaft. Disziplinäre und praktische Perspektiven)

Learning Data-Driven PCHD Models for Control Engineering Applications* - Junker, Annika; Timmermann, Julia; Trächtler, Ansgar (IFAC-PapersOnLine)
Keywords: Control and Systems Engineering

Museen sind wie Denkmäler - Hartung, Olaf (BBBank-Magazin Wertsache)
Keywords: Museum Geschichte Exponate

VALIDATION AND COMPARISON OF FEM-SIMULATION RESULTS OF THE FUSED DEPOSITION MODELING PROCESS UNDER CONSIDERATION OF DIFFERENT MESH RESOLUTIONS - Moritzer, Elmar; Hecker, Felix (Proceedings of the 33rd Annual Freeform Fabrication Symposium)

The broken chain: Evidence against emotionally driven upstream indirect reciprocity - Schnedler, Wendelin (Games and Economic Behavior)
Psychologists claim that being treated kindly puts individuals in a positive emotional state: they then treat an unrelated third party more kindly. Numerous experiments document that subjects indeed ‘pay forward’ specific behavior. For example, they are less generous after having experienced stinginess. This, however, is not necessarily driven by emotions. Subjects may also imitate what they regard as socially adequate behavior. Here, I present an experiment in which imitation is not possible at the next opportunity to act with a stranger: after being given either a fun or an annoying job, subjects have to decide whether to be generous or not. I find that although subjects who are given the annoying job report more negative emotions than those with the fun job, they do not treat an unrelated third person more unkindly in terms of passing on less money.
Keywords: Economics and Econometrics; Finance

Transfer Pricing Rules for Intangibles: Implementation and Practical Challenges - Safaei, Reyhaneh

Changes in Transfer Pricing Regulations and Corporate Investment Decisions - Shabestari, Mehrzad Azmi; Safaei, Reyhaneh

Effects of spherical fillers on the processability and mechanical properties of PA613 and PP-based LS dry blends - Kletetzka, Ivo; Gawlikowicz, Roland; Schmid, Hans-Joachim (Proceedings of the 33th Annual International Solid Freeform Fabrication Symposium)
In this work, the influences of spherical fillers on the processing properties and the resulting mechanical properties of laser sintered components are investigated. For this purpose, micro glass spheres, hollow glass bubbles and mineral spheres are dry blended to the matrix polymers polyamide 613 and polypropylene with a filling ratio of 20 and 40 vol%. First, relevant properties of the blends, such as powder flowability, thermal behavior and melt viscosity, are investigated. Based on the results, processing parameters are then developed for the LS process and the mechanical properties of the components are investigated. The aim is to be able to tailor the mechanical properties of LS components by adding fillers and thus to create new application areas for additively manufactured components.